Quantum mechanics 1 - Green, N. J. B. ([S.l.] : Oxford University Press, 1997)
Quantum mechanics is of central importance in chemistry. To understand matter and its chemical transformations it is necessary to take a microscopic view connecting experimental observation to the properties of constituent molecules. However, at this microscopic level atoms and sub- atomic particles do not obey the classical laws of mechanics that pertain to the everyday macroscopic world. They obey the laws of quantum mechanics. The aim of this book is to explain the fundamentals of quantum mechanics from the point of view of chemistry; to describe areas of chemistry where quantum mechanics is most important; and to show how quantum mechanics is applied to chemical problems. To this end, the book is divided into two parts: the first deals with the foundations of quantum mechanics (concentrating on exactly soluble problems and the reduction of complicated problems to simple foundations) and the second is a tool kit for applying quantum mechanics to chemical problems (thus concentrating on approximate methods). Although advanced mathematics has been kept to a minimum, the nature of the subject means a certain amount of mathematics is necessary and it is assumed the reader is familiar with a typical first year mathematics course. Quantum Mechanics is an intermediate level text aimed at second and third year undergraduates.
Keywords: quantum mechanics